If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 18 = 3y + 11 Reorder the terms: 18 + 2x = 3y + 11 Reorder the terms: 18 + 2x = 11 + 3y Solving 18 + 2x = 11 + 3y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-18' to each side of the equation. 18 + -18 + 2x = 11 + -18 + 3y Combine like terms: 18 + -18 = 0 0 + 2x = 11 + -18 + 3y 2x = 11 + -18 + 3y Combine like terms: 11 + -18 = -7 2x = -7 + 3y Divide each side by '2'. x = -3.5 + 1.5y Simplifying x = -3.5 + 1.5y
| 96-16b=12 | | 1.6=7.6-5k+5.5 | | 5x-12=69 | | 7n+18=6n-(n-9) | | 2v-4-5=-17.5 | | 2IN(3x+4)=0 | | 12x^4+2x^3-30x-5=0 | | x=62 | | 7n-18=6n+(n-9) | | 7p^2+75p+50= | | 7.5p=22.5 | | -7n+18=6n+(n-9) | | -2+3x=-6+13x | | 7n=7.9 | | 4d+6e-5d+4e= | | 24x+30x= | | 5x+6=5x-11 | | 1=5x+1 | | 4m-15=17 | | 6n+58=106 | | 44-2x=14-8x | | 174=4x+3(6x-8) | | s^2+3v-40= | | x^4-12x^3+216x-324=0 | | 3x+8=-27-2x | | g-500=225+g | | 2x+3x+4x-5=22+3+4x | | 2(2)-y=6 | | 7+4x=10+x | | 7n+18=6n+(n-9) | | x+3/4=4 | | 117=4(x+45)+3x |